Peran Sarana dan Prasarana oleh Tenaga Kependidikan dalam Mendukung Proses Pembelajaran yang Efektif di SMAN 1 Majalaya Karawang - Rizki Ramadhan; Laila Febriani Ulin Nikmah; Putri Meilani Mutiara Pribadi; Hinggil Permana (JISPENDIORA Jurnal Ilmu Sosial Pendidikan Dan Humaniora, 2025)
The purpose of this study is to examine the importance of infrastructure and facilities management in efforts to improve educational standards. A qualitative approach using literature study methodoogy. The results of the study indicate that infrastructure and facilities management is very important in efforts to improve educational standards, which are examined from the following perspectives: 2) Definition of infrastructure and facilities management, which includes efforts to utilize and manage facilities to support the educational process in schools; 1) Definition of infrastructure and facilities, which includes its role as a supporting element in achieving learning activities based on the curriculum in each educational unit; 3) Principles of infrastructure and facilities management, such as a) the principle of achieving goals, c) administrative principles, d) principles of clarity of responsibility, and e) principles of cohesion; 4) stages of management of facilities and infrastructure, including planning, acquisition, utilization, inventory, maintenance, and transfer; and 5) the relationship between the existence of facilities and infrastructure and the improvement of educational standards, where schools that have adequate facilities and infrastructure are usually better prepared to improve educational standards.